PENGARUH MODEL INKUIRI TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI DIKELAS V - Indah Permata Sari; Denny Wahyuni; Nur Zakiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the inquiry learning model on the learning motivation of fifth-grade students in Islamic Religious Education and Character Education at SDN 007 Sidomulyo, Lirik District, Indragiri Hulu Regency. The research employed a quantitative approach with a quasi-experimental design involving an experimental class and a control class. Data were collected through questionnaires, observations, and documentation, then analyzed using IBM SPSS version 25. Observation results indicated that the implementation of the inquiry learning model was carried out very well, with a percentage of 88.02%. The Shapiro–Wilk normality test showed that all data were normally distributed, while the Levene homogeneity test produced a significance value of 0.009 (< 0.05), indicating non-homogeneous data. Therefore, hypothesis testing was conducted using the Mann–Whitney U Test. The analysis revealed an Asymp. Sig. (2-tailed) value of 0.011 (< 0.05), indicating a significant difference between the experimental and control classes. The experimental class obtained a higher post-test mean score (82.08) than the control class (76.05). Furthermore, the effect size analysis yielded Cohen’s d = 0.822 and eta squared (η²) = 0.145, both indicating a large effect. These findings demonstrate that the inquiry learning model has a significant and substantial influence on students’ learning motivation in Islamic Religious Education.